Comparison of Radial Extracorporeal Shockwave Therapy versus Ultrasound Therapy in the Treatment of Rotator Cuff Tendinopathy - Vasileios Dedes; Konstantinos Tzirogiannis; Maria Polikandrioti; Ariadni Maria Dede; Christos Nikolaidis; Athanasios Mitseas; Georgios I. Panoutsopoulos (Folia Medica, 2019)
Introduction: People suffering from rotator cuff tendinopathy exhibit reduced mobility due to pain. The pain and the limited functionality affect negatively the overall quality of life.Aim: The present study aimed to investigate the intensity of pain, the functionality of the upper limbs and the quality of life of patients with rotator cuff tendinopathy by using two different therapeutic modalities, shockwave and ultrasound, whose outcomes were assessed pre-treatment and post-treatment as well as after a 4-week follow-up.Materials and methods: Out of the total sample of 115 patients with rotator cuff tendinopathy, 56 patients constituted the shockwave intervention group, 47 patients constituted the therapeutic ultrasound group and 12 patients made up the control group. The self-administered questionnaire “The University of Peloponnese Pain, Functionality and Quality of Life Questionnaire, UoP – PFQ” was used where the intensity of pain, functionality and quality of life of the upper limbs were evaluated on a five-point Likert scale, pre-treatment, post-treatment and at a 4-week follow-up.Results: The pain intensity was reduced and both the functionality and quality of life were improved after shockwave therapy post-treatment (p<0.001) and at a 4-week follow-up (p<0.001) compared with those found after the treatment. Similar improvements in all three parameters were also observed after ultrasound treatment but the outcomes were not as pronounced as in the shockwave group. Conclusion: Both radial shockwave and ultrasound therapies were found to be effective in the treatment of rotator cuff tendinopathy, the statistical analysis showing that radial shockwave therapy was superior to the ultrasound therapy post-treatment and at the 4-week follow-up.